Analisis Maqasid al-Shari‘ah atas Kebijakan Publik yang Mengandung Unsur Pemaksaan Kontrasepsi - Abadi, Briyan Maulana; Zahwa, Muhammad Faisol; Wildan, Adam Has (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
This study aims to analyze public policies that require vasectomy as a condition for receiving social assistance, using the maqasid al-shari‘ah approach. This study focuses on the study of the ethical, legal, and social implications of the policy, as well as its impact on individual reproductive rights. The method used is a qualitative method with descriptive analysis through the maqasid al-shari‘ah approach, which assesses the policy based on the objectives of Islamic law, namely protecting offspring, human dignity, and the individual's right to choose regarding reproductive health. The results of the study indicate that this policy is contrary to the basic principles of maqasid al-shari‘ah, especially in terms of hifz al-nasl (protecting offspring) and hifz al-‘ird (protecting individual dignity), and can lead to social injustice, discrimination, and potential violations of human rights. This study recommends changes to the policy with a more inclusive approach, respecting individual rights, and ensuring that social policies do not harm the reproductive rights of the community.